Identifying Concentration of Carbon Dioxide at Heights of 1.5 M and 15 M in Six Locations in Urban Areas - Huboyo, Haryono Setiyo; Manullang, Okto Risdianto; Samadikun, Budi P (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2022)
Several activities in urban areas emit CO2 gas and the amount of the emission is closely related to land use. This will, in turn, increase global warming phenomena in urban areas. So far, the estimation of pollutant concentrations in the ambient air has been carried out at the height of human breath, and very rarely the concentration values at low-level altitudes have been studied in Indonesia. This study tries to analyze the CO2 concentration based on different altitudes and different locations. Measurements of this study were carried out in industrial, residential, commercial, and highway areas using drones at two altitudes of 1.5 m and 15 m. The use of altitude variations to know the homogeneity of CO2 spatial distribution at different heights. The results of the study showed CO2 concentrations on weekday mornings and afternoons, and weekend mornings in the sampling areas at 1.5 m and 15 m in the range of 393 – 462 ppm and 391 – 460 ppm, respectively. The statistical test showed that there is no significant CO2 concentration difference between altitudes of 1.5 m and 15 m, with only a 0.17% difference value on average. The Tugu Industrial Estate area has the highest concentration of CO2, while the area on Jalan Perintis Kemerdekaan has the lowest concentration.